2018
DOI: 10.1111/josh.12702
|View full text |Cite
|
Sign up to set email alerts
|

School Food Policies and Student Eating Behaviors in Canada: Examination of the 2015 Cancer Risk Assessment in Youth Survey

Abstract: BACKGROUND: Limited evidence exists on effects of school-based nutrition policies. This study explored the influence of mandatory versus voluntary provincial school nutrition policies on student eating behaviors. METHODS:A cross-sectional, school-based survey assessed student eating behaviors using self-report survey measures in a representative sample of Canadian high school students from 7 provinces (N = 12,110). Provincial school nutrition policies were characterized as mandatory or voluntary. Healthful and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 26 publications
0
12
0
5
Order By: Relevance
“…Variation in the type of provincial-level school nutrition policies (e.g. mandatory v. voluntary) has been reported in Canada (37)(38)(39)(40) . For example, nutrition standards regarding the sale of foods and beverages in schools are voluntary in some provinces (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in the type of provincial-level school nutrition policies (e.g. mandatory v. voluntary) has been reported in Canada (37)(38)(39)(40) . For example, nutrition standards regarding the sale of foods and beverages in schools are voluntary in some provinces (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Non-compliance with school nutrition policies has been reported in studies examining beverages and foods sold in school vending machines in Alberta and Ontario (43,44) . Despite these variations in the implementation of school nutrition policies and guidelines, recent research has suggested no association between school nutrition policy enforcement level (mandatory v. voluntary) and school day dietary behaviours among Canadian youth and adolescents (40) . Our findings suggest that Canadian children's school hour dietary quality improved similarly across provinces from 2004 to 2015.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found over one third of Ontario secondary school students ate meals prepared by fast food restaurants at least once per week (23). Similarly, in an online survey of youth from 7 Canadian provinces, 27.4% reported buying lunch out three or more days a week and another 56.7% on one-to-two days, while 12.1% and 24.4% bought lunch at school three-to-ve and one-to-two days/week, respectively; only 15.9% of students did not buy lunch from a fast food restaurant, convenience store, or other off-campus option at all in the previous school week (24).…”
Section: Introductionmentioning
confidence: 99%
“…Lunches prepared at home are generally considered the most nutritious option, relative to meals purchased from fast food, restaurants, and convenience store outlets (24,23). In Canadian secondary school students, those who bring a home-packed lunch report better total dietary quality, and consume fewer SSBs (25) and more fruit, vegetable (26), and whole grain servings, compared to their peers who purchase lunch from school or off campus (24,27). For purchased lunches, most studies support the school cafeteria food as the healthier alternative to food purchased at fast food outlets or other restaurant and retail options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation